Current mode leapfrog ladder filters using a new active block - Ayten, Umut E.; Sagbas, Mehmet; Sedef, Herman (ELSEVIER GMBH, 2010)
In this paper, a new multi-terminal active component, namely current backward transconductance amplifier (CBTA) is proposed. The design procedure for the systematic realization of current-mode ladder filters using proposed active component is also presented. In order to demonstrate that the CBTA considerably simplifies the leapfrog structure of the current-mode ladder filters, a fifth-order Butterworth low-pass filter that requires a minimum of active components is presented. The theoretical results are demonstrated by using PSPICE simulation. (C) 2009 Elsevier GmbH. All rights reserved.
Keywords: Current backward transconductance amplifier; Current-mode; Leapfrog ladder filters; Active filters; Signal flow graph; DIFFERENCING BUFFERED AMPLIFIER; FLOATING INDUCTANCE; MINIMUM NUMBER; PASS FILTERS; REALIZATION; CIRCUIT; Engineering; Telecommunications